Video games and urban simulation: new tools or new tricks? - Samuel Rufat; Hovig Ter Minassian (Cybergeo, 2012)
Video games allow complex systems modelling, revealing retroaction loops, replicating self-organization and the emergence of hierarchical organization, functional differentiation and social segregation through multi-level interactions. Recent trends focus on improving modelling tools’ graphic quality and interface attractiveness and on using video games to facilitate urban studies teaching and research. This apparent convergence between simulation and video games is addressed through a selection of strategy and city builder video games. Comparisons reveal that simulations and video games point to similar results:, they both allow the simulation of complex urban processes, like hierarchical urban networks or urban segregation. Games even seem to allow going one step further, being often more comprehensive simulations. However, the main limitation of video games emerges from their didactic power: video games and simulation software implement rules and models in almost opposite means. Games induce players to learn the model but not to challenge or to produce new knowledge.